The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2147/amep.s21201
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of an educational program on nursing students’ caring and self-perception in intensive clinical training in Jordan

Abstract: BackgroundFraming and development of clinical skills in nursing students during their clinical practice is critical because this can shape their future caring skills. Professional caring empowers patients and contributes to their well-being and health. Education may enhance the capacity of nurses to be effective caring practitioners. Their study program encourages caring behavior in nursing students, consequently affecting their professional self-perception.MethodsThe present study investigated the effect of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
2
7
0
2
Order By: Relevance
“…Self-care practices related to the consumption of medication in table (2) shows that the control group recorded no significant differences, compared with the posttest of the study group which pointed highly significant changes among the study group members after involving in an educational program. These results agree with the study that conducted in two critical care units in the Ma'an and Queen Rania hospitals in the south of Jordan in line of this study reported that effective educational intervention shows significant difference to enhance self-care practices among patients with specific diseases when assessed (Khouri, 2011). Alteration of the psychosocial aspects which play important factors which increase trigger of seizure in epileptic patients, table (3) shows that there is a significant difference clearly appears among the post test of the study group members who participated in the educational program sessions which included advices and suggestions to enhance self-management and improve coping mechanism in order to decrease the triggers of the seizure, while no significant differences indicated among the pre and post-test of the control group members, this result was paralled with (Otsu H, and Moriyam, 2014) who found that significant responses were detected among patients.…”
Section: Discussionsupporting
confidence: 92%
“…Self-care practices related to the consumption of medication in table (2) shows that the control group recorded no significant differences, compared with the posttest of the study group which pointed highly significant changes among the study group members after involving in an educational program. These results agree with the study that conducted in two critical care units in the Ma'an and Queen Rania hospitals in the south of Jordan in line of this study reported that effective educational intervention shows significant difference to enhance self-care practices among patients with specific diseases when assessed (Khouri, 2011). Alteration of the psychosocial aspects which play important factors which increase trigger of seizure in epileptic patients, table (3) shows that there is a significant difference clearly appears among the post test of the study group members who participated in the educational program sessions which included advices and suggestions to enhance self-management and improve coping mechanism in order to decrease the triggers of the seizure, while no significant differences indicated among the pre and post-test of the control group members, this result was paralled with (Otsu H, and Moriyam, 2014) who found that significant responses were detected among patients.…”
Section: Discussionsupporting
confidence: 92%
“…This result is congruent with Aslani et al [8], who showed that nurses' knowledge and practice of using needles with appropriate diameter was good but they did not have correct and scientific knowledge of indications and method of heating blood. In addition, Khouri [27] reported that the education may enhance the capacity of nurses to be effective caring practitioners. Additionally, Hijji et al [15] high lighted that preventing and recognizing a transfusion reaction requires nurses to have adequate knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Many baccalaureate programs offer brief experiences for students in critical care units and some limited only to the clinical experiences [4,17]. Some studies have focused on determining the adequacy of theoretical knowledge and skills of students than the multidimensional experiences of students [13,17].…”
Section: Journal Of Intensive and Critical Care Issn 2471-8505mentioning
confidence: 99%
“…These include good and bad days, confidence and conscious incompetence. It is appear that the interactions between support, knowledge and skills and socializations enabled participants to move on [17] and selecting career path and where the students need to be. In addition to the interpersonal interaction between students, staff preceptors and faculty members.…”
Section: Selecting Career Pathmentioning
confidence: 99%